The development of the Arctic as a business region : A stakeholder perspective - Perkkola, Anna (2018)
The Arctic region has several unique characteristics. Due to its young age as a region and the remote location, the amount of academic research on the Arctic is still very limited. The Arctic region has recently been in the headlines for its environmental aspects, especially for the impacts of the climate change. The region is also believed to offer great opportunities for various business like marine transportation and natural resource extraction. The objective of the study was to examine how to develop the Arctic region in a way that it supports the arctic business. This was done by identifying the arctic stakeholders and by investigating how the different stakeholders perceive business opportunities and challenges in the region and what kind of expectations are set for the Arctic region’s development from these different stakeholders’ perspectives. The study follows an empirical research approach. It was realised as a qualitative research and the data were collected in semi-structured theme interviews. Altogether nine representatives of different arctic stakeholder groups were interviewed for the study. Based on the results, the most important arctic stakeholders are local and indigenous peoples, arctic governments, arctic business, the Arctic Council, environmental organisations & other NGOs and non-arctic governments & other non-arctic parties. The results also indicate that the most prominent business opportunities are concentrated on tourism, infrastructure, maritime business, environmental business and extractive industry. The biggest challenges for business in the region are related to complex legislation, physical environment and lack of cooperation and knowledge. The results show that the stakeholders’ expectations for the arctic development are not in line. The balance between the economical and environmental aspects poses the main difficulty for achieving a common vision. The findings of the study suggest the Arctic region to have a sustainable development approach, which will take into account both economical and environmental aspects. In the long run the sustainable approach is the only way to guarantee continuous business opportunities also in the future. For arctic business the chosen approach would mean either transforming into more sustainable form or creating new sustainable business models. Successful implementation of the sustainable development in to the Arctic region requires above all support for the arctic companies and increased cooperation among the arctic stakeholders.